Cabo Verde : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Cabo Verde. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2018)
This 2018 Article IV Consultation highlights that the economic recovery in Cabo Verde is gaining momentum, reflecting a more favorable external environment and the payoff of ongoing economic reforms. In 2017, the economy is estimated to have expanded by 4 percent supported by the double digit-growth in tourist arrivals, the recovery in credit to the private sector, and stronger consumer and business confidence. These factors are expected to boost growth further to 4.3 percent in 2018. Over the medium term, real GDP growth is projected to stabilize at about 4 percent. Financial stability indicators have improved but the level of nonperforming loans remains elevated.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet